Vitamin D in relation to bone health and muscle function in young female soccer players - Brännström, A.; Yu, J.-G.; Jonsson, P.; Åkerfeldt, T.; Stridsberg, M.; Svensson, M. (European Journal of Sport Science, 2017)
The present work investigated serum vitamin D (25(OH)D) status in relation to bone and muscle qualities and functions in 19 female soccer players (13-16 years) resident at northern latitude with very low sun exposure (~32-36 h/month) during winter season (late January to early March). Serum 25(OH)D, parathyroid hormone and bone turnover markers osteocalcin (OC) and beta carboxy-terminal collagen cross-links (ß-Ctx), as well as body composition and muscle performance were examined. Hormones were tested using routine laboratory methods. Fat mass, lean mass, and bone mineral density in whole body, as well as femur and lumbar spine were evaluated with dual-energy X-ray absorptiometry. Muscle performance was assessed through isokinetic knee extension and flexion, countermovement jump, and sprint running. 25(OH)D was low (50.5 ± 12.8 nmol l-1), whereas the values of bone turnover markers were markedly high (OC: 59.4 ± 18.6 µg l-1; ß-Ctx: 1075 ± 408 ng l-1). All bone and muscle measurements were normal or above normal. 25(OH)D was not significantly correlated with most of the parameters of bone and muscle quality or function, except the knee extension time to peak torque (r = -0.50, p?=?.03). In conclusion, the level of vitamin D is markedly low in adolescent female soccer players during the winter in Sweden. However, vitamin D levels did not significantly correlate with measures of bone and muscle except a moderate correlation in time to peak torque in the knee extensors. The practical implication of low vitamin D levels in young growing female athletes remains unclear